Characteristics of selected methods of risk assessment - Kowalczyk, Anna; Chodoła, Izabela; Kulczycka, Kinga; Stychno, Ewa (Journal of Education, Health and Sport, 2018)
The risk assessment forms the basis for the employer's use of work organisation and the creation of workplaces to protect employees against accident risks and the impact of harmful and disruptive factors. Risk assessment is also the basis for the identification and elimination by the employer of risks to the health and life of workers through the use of appropriate technologies, equipment, materials and substances that do not cause such risks. In cases where it is not possible to reduce the risk by this route, the employer is obliged to apply appropriate collective protection measures and, as a last resort, personal protective equipment. If significant changes are introduced, the occupational risks associated with the new risks must be assessed. Each time new machinery is purchased, new substances or technologies are introduced which may give rise to new risks, the risks involved must be reassessed. The aim of this work is to characterise the selected methods by which a comprehensive risk assessment can be carried out at the workplace.